The Influence of Education, Work Experience, and Individual Characteristics on Employee Performance at PT Mohandas Oeloeng, Semarang. - Dwi Ariyani, Meliana; Fajri, Annisa (Jurnal Manajemen, 2026)
This study aims to examine the influence of education, work experience, and individual characteristics on employee performance at PT Mohandas Oeloeng Semarang. This study is motivated by the importance of improving employee performance in the construction sector, which demands practical skills and experience in the field. The method chosen for this study is quantitative research with a sample of 60 workers selected using purposive sampling techniques. Data acquisition was carried out using questionnaires and analyzed using multiple linear regression analysis and using SPSS. The findings of this research are that work experience or knowledge has a positive and significant impact on employee performance. Conversely, education and individual characteristics have no other impact on employee performance. However, simultaneously, education, work knowledge, and personality characteristics have a positive and significant impact on employee performance. The results show that work experience as a variable has a positive and significant influence on employee performance, namely variables in the construction sector, while education and individual characteristics play a supporting role in the context of organizations that have a standardized work system.